2006
DOI: 10.1080/14639230600597820
|View full text |Cite
|
Sign up to set email alerts
|

Radiological clinical telesession: A cooperative working environment for sharing clinical experienceover the Internet

Abstract: We describe here a six-year-long project during which groups of radiologists belonging to various hospitals in Extremadura (one of Spain's regions) shared their clinical experience over the Internet in a process of continuing medical education. We designed a set of tools based on the most familiar Internet protocols (the WWW and e-mail) that make computer-mediated communication very straightforward. Periodically, each group put forward a clinical case of interest, presenting it on a Web page. The other partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the experience of presenters and students improved after exchanging educational information between peers in an online setting 35,36 . Participants in this survey also believe that the reception of lectures from experts in the field were advantageous.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have shown that the experience of presenters and students improved after exchanging educational information between peers in an online setting 35,36 . Participants in this survey also believe that the reception of lectures from experts in the field were advantageous.…”
Section: Discussionmentioning
confidence: 77%
“…Vega et al present “a cooperative working environment for sharing clinical experience over the Internet” [30]. Although focusing on image data, the presented solution is very similar to SOMWeb in terms of objectives and in focusing on “clinical sessions,” which in purpose and structure correspond to our “meetings.” However, the cases presented in clinical sessions are not formalized to the extent our cases are, and Semantic Web technologies are not used.…”
Section: Discussionmentioning
confidence: 99%
“…67 The sessions consisted of clinical case presentations, discussions of clinical findings, differential diagnoses, and suggestions, ultimately leading to a definitive diagnosis. Initially, three groups of radiologists joined the cooperative working environment and shared their clinical experience over the Internet.…”
Section: New Evidencementioning
confidence: 99%